Transformasi Teologi Misi Dalam Pendidikan Kristen Anak Usia Dini: Perspektif Akademik - Fewi Herman Harefa; Yusak Agus Setiawan; Lasmauli Gurning (Jurnal Silih Asuh : Teologi dan Misi, 2024)
Christian education in early childhood plays an important role in shaping the character, morals, and beliefs of children. This article discusses the importance of Christianity in the early stages of development, mission theology as the primary foundation, and the transformation in childhood Christianity. This transformation was realized in an effort to integrate Christian values into children's everyday lives, using technology, and collaborating with parents and communities. With a strong foundation of faith from an early age, children can face the challenges of life with strong conviction and morality.